An Analysis of Translation Techniques of Cursing Terms in English Subtitle of Lara Ati Movie - Zefanya, Charissa; Ekawati, Rosyida (Talenta Publisher, 2025)
This study is conducted to discuss in more detail about a translators strategy to translate the source language (SL) into the target language (TL), in particular the translation about cursing terms in movie Lara Ati. It is a descriptive qualitative design. This study focuses on swear words, phrases and sentences produced by the cast. The data in this study were collected through several steps, namely watching, identifying, making notes, and classifying the data. This study used Andersson & Trudgill (1990) theory and Molina and Albir (2002) theory. The results show the techniques most often used by translators are adaptation and amplification with 5 frequencies each. This study also found that the most frequent swear word in the movie